Why do rural residents in China withdraw from the health insurance system? —A qualitative study based on Y County in S Province, China - Ying Zuo; Guang Yang; Haoxuan Cheng; Lufa Zhang (BMC Public Health)
Abstract Background Since the 2009 healthcare reform, the Chinese government has been committed to establishing a universal healthcare system. This study aims to investigate the complex reasons behind rural residents’ decision to forgo participation in the medical insurance system by examining causal relationships and interactions. Methods This study employs content analysis, conducting in-depth interviews with 42 stakeholders, including government administration departments, tax departments, medical insurance departments, village committees, and residents who have withdrawn from the health insurance system. Results The study finds that the primary reasons rural residents withdraw from the medical insurance system are fourfold: heavy economic burdens, unfair design of the medical insurance system, failure of conventional mobilization strategies, and the internet’s impact on residents’ cognitive biases. Conclusion The decision of rural residents in China to withdraw from the medical insurance system is influenced not only by economic factors but also by the system’s design and various aspects of rural governance. Moving forward, the Chinese government should optimize the medical insurance system’s design, implement more flexible mobilization and persuasion strategies, and prioritize the identification and regulation of misleading information.